History and clinical examination at a glance - Gleadle, Jonathan (The at a glance series, 2012)
Every medical student must be able to take an accurate history and perform a physical examination. This third edition of History and Clinical Examination at a Glance provides a concise, highly illustrated companion which will help you develop these critical skills as you practice on the wards